Using WhatsApp as a medium of postgraduate instruction in a private university in Nigeria: fall-outs of the Covid-19 Pandemic - Aderinola Ololade Dunmade; Tella Adeyinka; Femi Kunle Aramide; Akinade Adebowale Adewojo (Universidade Estadual de Maringá, 2023)
The Covid-19 pandemic resulted in a global lockdown and the cessation of all academic activities on-site. Higher education in Nigeria was not exempt, as a paradigm shift was required for university officials to explore non-conventional teaching methods to prevent students from wasting time and to keep them intellectually engaged. During the pandemic, our research examines how a private institution in Ede, Osun State, Nigeria, utilised the social networking platform WhatsApp for Ph.D. student seminars. The study obtained data from ten doctoral students in the Department of Library and Information Science at Adeleke University via online interviews. The difficulties faced by the students and the benefits of utilising ICT were highlighted. Due to the constant insecurity and poor road network in Nig eria, as well as the risk of long-distance travel, especially for postgraduate students who are not always resident on campus, we recommend the continued use of E-learning platforms in Higher Education Institutions as a solution to reducing transportation costs.